2017
DOI: 10.1002/ptr.5840
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacognosy, Phytochemistry and Pharmacological Properties ofAchillea millefoliumL.: A Review

Abstract: Achillea millefoilum L. (Yarrow) is an important species of Asteraceae family with common utilization in traditional medicine of several cultures from Europe to Asia for the treatment of spasmodic gastrointestinal disorders, hepatobiliary, gynecological disorders, against inflammation and for wound healing. An extensive review of literature was made on A. millefoilum L. using ethno botanical text books, published articles in peer-reviewed journals, unpublished materials and scientific databases. The Plant List… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
103
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(136 citation statements)
references
References 127 publications
2
103
0
7
Order By: Relevance
“…It is one of the most frequently used plant drug in Serbia (Tucakov, 1984). Upper parts of the plant collected during the blooming are recognized as an anti-inflammatory, antinociceptive, spasmolytic, antimicrobial and holagog drug (Nadim et al, 2011;Cavalcanti et al, 2006;Benedek et al, 2008;Ali et al, 2017). Yarrow preparations in the form of infusions, decoctions or fresh juices have been applied against various indications such as anorexia, stomach cramps, flatulence, gastritis, enteritis, internal and external bleeding (Willuhn, 2002;Wichtl, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the most frequently used plant drug in Serbia (Tucakov, 1984). Upper parts of the plant collected during the blooming are recognized as an anti-inflammatory, antinociceptive, spasmolytic, antimicrobial and holagog drug (Nadim et al, 2011;Cavalcanti et al, 2006;Benedek et al, 2008;Ali et al, 2017). Yarrow preparations in the form of infusions, decoctions or fresh juices have been applied against various indications such as anorexia, stomach cramps, flatulence, gastritis, enteritis, internal and external bleeding (Willuhn, 2002;Wichtl, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that this plant has antimicrobial, antioxidant, and anti-inflammatory effects which are very important in the process of wound healing (Ali, Gopalakrishnan, & Venkatesalu, 2017;Stojanović, Radulović, Hashimoto, & Palić, 2005;Varasteh-kojourian et al, 2017). The antimicrobial properties of this plant are due to compounds such as flavonoids, terpenes, hydroxycamptothecinand saponins (Mothana, Lindequist, Gruenert, & Bednarski, 2009;Stojanović et al, 2005;Yaghoubi, Gh, & Satari, 2007).…”
mentioning
confidence: 99%
“…Achillea millefolium (yarrow) is native to temperate regions of the Northern Hemisphere but has been introduced worldwide [510]. The traditional medical uses of A. millefolium have been reviewed and the plant has been used since ancient times as a wound-healing agent and to treat gastrointestinal complaints [510][511][512]. Consistent with this, the Cherokee have also used A. millefolium as an antihemorrhagic; for healing wounds, treating bloody hemorrhoids and bloody urine, and for bowel complaints [15,17,510].…”
Section: Cherokee Aromatic Medicinal Plants Currently In Use As Herbamentioning
confidence: 99%